Pengaruh Risiko Spesifik Bank dan Good Corporate Governance Terhadap Stabilitas Bank Pembiayaan Rakyat Syariah - Muhamad Fakhrudin; Ahmad Fatoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to examine the influence of specific bank risks and Good Corporate Governance (GCG) on the stability of Sharia rural banks in the Province of Banten. The indicators of specific bank risks include Non-Performing Financing (NPF), Operational Cost to Operating Income (BOPO), and Capital Adequacy Ratio (CAR). Meanwhile, the indicators used to assess GCG are the size of the Sharia Supervisory Board (DPS), board of commissioners, and board of directors. This study uses panel data from 8 Sharia rural banks as research samples from June 2020 to June 2022. Based on the regression results using the selected model, which is the Common Effect Model, it was found that partially, the variables CAR, BOPO, and the board of directors have a significant influence on the stability of Sharia rural banks. Meanwhile, simultaneously, all the variables, namely NPF, CAR, BOPO, DPS, board of commissioners, and board of directors, collectively influence the stability of Sharia rural banks in the Province of Banten.